An HBCU track-and-field student-athlete perspective on the role of the pharmacist and physical therapist in sports - Blair Yesko; Yunghon Lee; Michael C. Rabel; Hoai-An Truong (Exploratory Research in Clinical and Social Pharmacy, 2023)
Background: Pharmacy is a profession with the capacity to provide services in a variety of venues, including sports and sporting events. The physical therapy profession is often involved in treating the injured athlete; however, direct interactions with collegiate sport teams is limited and inconsistent. A literature review showed a limited and inconsistent role of the pharmacist and physical therapist in sports, especially at Historically Black Colleges and Universities (HBCU). Objective: To examine collegiate track-and-field student-athlete perceptions related to the role of the pharmacist and physical therapist. Methods: A cross-sectional study using a convenience sample was conducted to assess the perceptions of NCAA track-and-field student-athletes from a HBCU. A survey utilizing modified Likert-scale and open-ended questions was administered electronically to fifty-four student-athletes via email. Inclusion criteria were age ≥ 18 years old and a current track-and-field student-athlete. Descriptive statistics were used for data analysis. Results: This study, one of the first to examine an HBCU student-athlete population, yielded a 100% response rate. About 80% want to discuss the directions for use and side effects of certain medications or dietary supplements with a team pharmacist. Over 75% of student-athletes desired to consult with a physical therapist about injury management and prevention. Overall, most respondents felt that pharmacists (81.5%) and physical therapists (78.8%) should have a role with NCAA sports to benefit student athletes. Conclusion: Interprofessional collaboration and communication among healthcare professionals is essential to improve student-athlete health knowledge and performance. The student-athletes expressed interests in receiving consultation and educational sessions from pharmacists and physical therapists.